Ethnic and cultural influences on body composition, lifestyle and body image among males - Kagawa, Masaharu (Curtin University, 2004)
The aim of this research was to determine ethnic and cultural influences on body composition, lifestyle, and aspects of body image (perception, acceptability, and satisfaction) of younger (age 18-40 years) Australian and Japanese males, the latter including groups living in Australia and Japan. The sample sizes of the three groups were 68 Japanese living in Australia, 84 Japanese living in Japan, and 72 Australian Caucasian males respectively. The methodology included body composition assessments (by anthropometry and DXA), lifestyle and body image questionnaires, and dietary records. The study found significant p<0.05) ethnic differences in the %BF at given BMI levels and for Japanese the BMI values of 23.6kg/m2 and 28.6kg/m2 were found to be equivalent to 25 and 30 for Caucasians when used to classify individuals as "overweight" and "obese". Equations in common use for the calculation of body composition in Japanese males were evaluated using modern methods of body composition assessment and found to need considerable modification. New regression equations that represent BMI-%BF relationships for Japanese and Australians were proposed: Japanese: Log %BF = -1.330 + 1.896(log BMI), (R2 = 0.547, SEE = 0.09); Australians: Log %BF = -1.522 + 2.001(log BMI), (R2 = 0.544, SEE = 0.10). Equations were also developed to predict %BF for Japanese and Australian males from body composition assessments using anthropometry and DXA: Japanese: %BF = 0.376 + 0.402(abdominal) + 0.772(medial calf) + 0.217(age), (R2 = 0.786, SEE = 2.69); Australians: %BF = 2.184 + 0.392(medial calf) + 0.678(supraspinale) + 0.467(triceps), (R2 = 0.864, SEE = 2.37). Lifestyle factors were found to influence perceptions of body image.Australian males participate in physical activity more frequently than their Japanese counterparts (Australians = 98.6% involved in vigorous activity at least once per week, Japanese living in Japan = 85.7%, Japanese living in Australia = 72.1%). Significant differences p<0.05) in energy contribution patterns were found between the Japanese group (Protein: 14.4%, Carbohydrate: 50.4%, Fat: 28.1%) and Japanese living in Australia (JA: Protein: 16.3%, Carbohydrate: 47.3%, Fat: 32.3%) and the Australians (Protein: 17.1%, Carbohydrate: 47.9%, Fat: 30.6%). This shows that the Japanese living in Australia have adopted a more westemised diet than those living in Japan. Body Image assessments were done on all study groups using the Somatomorphic Matrix (SM) computer program and questionnaires, including the Ben-Tovim Walker Body Attitudes Questionnaires, (BAQ) the Attention to the Body Shape Scale (ABS), and the Eating Attitudes Test (EAT). Japanese males tended to overestimate their weight and amount of body fat, while Australian Caucasian males underestimated these parameters. The Japanese groups had higher scores on the selfdisparagement subscale and lower scores on the strengths and the attractiveness subscales of the BAQ questionnaire than Australian males. Australian males also had higher scores on the EAT total score and the dieting subscale of the EAT questionnaire than Japanese males. When all groups of subjects selected their perceived body image from the SM program menu, these results had no relationship with measured body composition values, suggesting that further development of this program is needed for use in these populations.